2020
DOI: 10.4293/jsls.2020.00072
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Social Media Use for Surgical Education During Covid-19

Abstract: Objective: To evaluate the use of social media platforms by medical students, surgical trainees, and practicing surgeons for surgical education during the Covid-19 pandemic.Methods: An online, 15-question survey was developed and posted on Facebook and WhatsApp closed surgeon groups.Results: The online survey was completed by 219 participants from South America (87%), North America (7%), Europe (5%), Central America, and Asia. Respondents included medical students (6.4%), surgical residents/fellows (24.2%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Again similar to our results, Goshtasbi et al reported that larger residency programs more often had Instagram accounts and had more followers/posts, which may be due to the need to recruit more residents and increased interest in larger programs with more positions 8 . These accounts are also windows into the more intangible aspects of residency, including resident life, program culture, research opportunities, and social justice initiatives 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Again similar to our results, Goshtasbi et al reported that larger residency programs more often had Instagram accounts and had more followers/posts, which may be due to the need to recruit more residents and increased interest in larger programs with more positions 8 . These accounts are also windows into the more intangible aspects of residency, including resident life, program culture, research opportunities, and social justice initiatives 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Residents have to work in the pandemic clinics rather than their clinics due to the shortage of consultants and surgical teams due to the COVID-19 pandemic. The negative impact on global healthcare systems of the closure of academic institutions due to the pandemic should not be underestimated [ 14 ]. Considering all the above, the COVID-19 pandemic can be seen to have had an enormous impact on the quantity and quality of training, for both medical and surgical residents, and this problem can be more clearly understood from the difficulties encountered when medical students and residents graduate without adequate training and must serve at the forefront of the field [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many COVID-19 themed WhatsApp groups have been formed among clinical teams, enabling trainees to share resources, guidelines, pertinent research articles and clinical experiences. 16 Similarly Twitter has provided a dynamic forum for signposting to COVID-19 resources and sharing knowledge. 17 WhatsApp groups between team members have also provided an important support network for trainees.…”
Section: Digital Technologiesmentioning
confidence: 99%